Tackling a deadly global phenomenon: sepsis induced coagulopathy: a narrative review - Ainan Arshad; Ahmed, Warda; Rehman, Naureen; Naseem, Zehra; Ghos, Zara (Journal of the Pakistan Medical Association, 2024)
Sepsis is a potentially fatal illness marked by organ failure and the two main causes of which are shock and disseminated intravascular coagulation. Multi-organ dysfunction in sepsis is mediated by the inflammatory cytokine storm, while sepsis induced coagulopathy is mediated and accelerated by activation of pro-coagulative mechanisms. Regardless of the severity of sepsis, disseminated intravascular coagulation is a potent predictor of mortality in septic patients. Additionally, oxidative stress in sepsis causes renal ischemia and eventually acute kidney injury. The first and foremost goal is to initiate resuscitation immediately, with treatment mainly focusing on maintaining a balance of coagulants and anticoagulants. A simpler and more universal diagnostic criteria is likely to improve studies on the spectrum associated with sepsis. Key Words: Sepsis induced coagulopathy, Anticoagulants, Coagulants, DIC.